Comparative analysis of achievements of eighth-grade students of civic education and students of religioous education on ICCS 2022 study - Ranđelović Branislav M.; Trbojević Tanja M.; Đukić Danijela P. (Zbornik radova (Univerzitet u Kragujevcu. Pedagoški fakultet u Užicu))
ICCS is one of the international surveys that is carried out in a large number of educational systems around the world. It deals with students' knowledge and attitudes regarding civic responsibilities and active participation in society. This study covers areas that are considered to be increasingly important in today's modern society: sustainable development and global citizenship education, migration and diversity, digital citizenship education (the use of ICT to participate in social and political events), young people's views on political systems (trust in institutions, system, media) and individual feeling of freedom and security. Given the similarities covered in ICCS research and the curriculum of Civic Education, the logical question is whether the achievements of students attending Civic Education and those students attending Religious Education are different. If there is a certain difference in student achievement, it can be rightly concluded that attending Civic Education classes creates a certain positive effect on students. The main goal of this research is to examine the relationship between student achievement on the ICCS 2022 test and whether they attend Civic Education or Religious Education. The results point to the conclusion that attending Civic Education has a positive effect on students' knowledge, as well as that it contributes to students' better knowledge of democracy. This can be attributed to the quality system support of education to promote democratic principles and the development of such beliefs in students